2018
DOI: 10.5194/acp-18-327-2018
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous reaction of HO<sub>2</sub> with airborne TiO<sub>2</sub> particles and its implication for climate change mitigation strategies

Abstract: Abstract. One geoengineering mitigation strategy for global temperature rises resulting from the increased concentrations of greenhouse gases is to inject particles into the stratosphere to scatter solar radiation back to space, with TiO 2 particles emerging as a possible candidate. Uptake coefficients of HO 2 , γ (HO 2 ), onto sub-micrometre TiO 2 particles were measured at room temperature and different relative humidities (RHs) using an atmospheric pressure aerosol flow tube coupled to a sensitive HO 2 dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…when the condensed-phase copper ion concentration is less than 1-2 × 10 −4 M, the heterogeneous uptake of HO 2 is not significant and may mainly be driven by the self-reaction of HO 2 . This threshold is consistent with the results of previous research studies (Mozurkewich et al, 1987;Lakey et al, 2016b). The threshold is also consistent in different heterogeneous media of aerosol and cloud or rain droplets.…”
Section: Model Validationsupporting
confidence: 93%
See 2 more Smart Citations
“…when the condensed-phase copper ion concentration is less than 1-2 × 10 −4 M, the heterogeneous uptake of HO 2 is not significant and may mainly be driven by the self-reaction of HO 2 . This threshold is consistent with the results of previous research studies (Mozurkewich et al, 1987;Lakey et al, 2016b). The threshold is also consistent in different heterogeneous media of aerosol and cloud or rain droplets.…”
Section: Model Validationsupporting
confidence: 93%
“…Since there is no direct evidence of the existence of Cu/Fe redox reactions of HO 2 which produce H 2 O rather than H 2 O 2 as proposed by Mao et al (2013), in the scope of this paper, HO 2 uptake produces H 2 O separately by Cuand Fe-free ions as proposed by many research studies (Mozurkewich et al, 1987;Hanson et al, 1992;Thornton and Abbatt, 2005;Thornton et al, 2008;Taketani et al, 2009;Macintyre and Evans, 2011). Fe-free ions can be seen as the equivalent Cu-free ions in the application of the MARK model or the parameterized equation mentioned below.…”
Section: Aerosol Particle Condensed-phase Cu 2+ Molality Calculationmentioning
confidence: 85%
See 1 more Smart Citation
“…On dry aerosol surfaces, γ(HO 2 ) is usually low: For example, Bedjanian et al (2005) measured γ(HO 2 ) = 0.075 ± 0.015 on dry soot surfaces which is comparable to the value of γ(HO 2 ) ≤ 0.031 on dust (Matthews et al, 2014) and γ < 0.01 on dry NaCl (Remorov et al, 2002). γ(HO 2 ) increases by more than one order magnitude when RH increases from ∼20% to > 90% (Cooper and Abbatt, 1996;Taketani et al, 2008;Lakey et al, 2015Lakey et al, , 2016Moon et al, 2018). Lakey et al (2015) showed much higher γ(HO 2 ) values on two humic acids (0.0007 ≤ γ(HO 2 ) ≤ 0.06 and 0.043 ≤γ(HO 2 ) ≤ 0.09, respectively) than on pure long-chain carboxylic acids (γ(HO 2 ) < 0.004).…”
Section: Reactive Uptake Coefficient Of the Hydroxy Peroxyl Radical γ(Ho 2 )mentioning
confidence: 78%
“…However, the majority of aerosols, >90 %, had diameters in the range that could be directly detected. Previously, we had determined by imaging the aerosols using a scanning electron microscope (SEM) that the particles were spherical (Moon et al, 2018…”
Section: Aerosol Generation and Detectionmentioning
confidence: 99%